2021
DOI: 10.3390/foods10051060
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Grain- and Grass-Finishing Systems on Carcass Characteristics, Meat Quality, Nutritional Composition, and Consumer Sensory Attributes of Bison

Abstract: The objective of this study was to determine the influence of two finishing systems (grain- or grass-finishing) on carcass characteristics, meat quality, nutritional composition, and sensory attributes of bison. Bison heifers were assigned to either a grain- or grass-finishing treatment for 130 days prior to slaughter. Carcass measurements, lean color and fat color were recorded. Striploins (M. longissimus lumborum) were collected for analysis of pH, fatty acid profile, cholesterol, proximate analysis, Warner-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 80 publications
2
2
1
Order By: Relevance
“…No difference in PUFA and PUFA:SFA ratio was observed among the three bovine groups in this study. The PUFA:SFA ratios were all below the ratio (0.4) recommended by the World Health Organization ( 98 ), which is consistent with the reported values for cattle (~0.1) ( 54 , 99 ), but lower than values reported for yaks (0.4–0.6) ( 100 ) and bison (0.4–0.6) ( 101 ). The atherogenic index (AI) and thrombogenicity index (TI) are related to the incidence of coronary heart disease ( 80 , 102 ); there was no difference in these indices among GY, FC, and FY in this study.…”
Section: Discussionsupporting
confidence: 89%
“…No difference in PUFA and PUFA:SFA ratio was observed among the three bovine groups in this study. The PUFA:SFA ratios were all below the ratio (0.4) recommended by the World Health Organization ( 98 ), which is consistent with the reported values for cattle (~0.1) ( 54 , 99 ), but lower than values reported for yaks (0.4–0.6) ( 100 ) and bison (0.4–0.6) ( 101 ). The atherogenic index (AI) and thrombogenicity index (TI) are related to the incidence of coronary heart disease ( 80 , 102 ); there was no difference in these indices among GY, FC, and FY in this study.…”
Section: Discussionsupporting
confidence: 89%
“…The relatively favorable omega-6 to omega-3 ratio in the pen-nished bison is likely because of the freechoice feed arrangement in this study, allowing the animal to self-regulate intake of corn in addition to having access to alfalfa and meadow hay, which are relatively rich in alpha linolenic acid (ALA). Ratios in this study are also lower than previous work in bison, which found an omega-6 to omega-3 ratios of 5.74 and 4.64 in grain-fed and pasture-nished bison heifers, respectively [23]. With regard to individual omega-3 fatty acids, eicosapentaenoic acid (EPA), docosapentaenoic acid (DPA) were signi cantly elevated in pasture-nished bison (Table 5).…”
Section: Lipid Metabolitescontrasting
confidence: 70%
“…The results of the proximate analysis are shown in Table 2. Previous work comparing the in uence of nishing mode in bison (pasture-nished vs pen-nished) found that pen-nished bison contained 1.3 g more fat per 100 gram when compared to pasture-nished animals [23]. Pasture-nished bison in the current study were also leaner (1.9 g less fat per 100 gram) compared to the pen-nished bison.…”
Section: Proximate Analysissupporting
confidence: 53%
“…The feeding system has effects on beef quality since the nutrient composition and energy intake of the diet can affect the animal’s growth rate, degree of maturity, and carcass composition, particularly the amount of IMF and the FA profile [ 87 ]. Diet composition and finishing management have different effects on beef quality traits, especially for different animal categories.…”
Section: Main Factors Affecting Beef Eating Qualitymentioning
confidence: 99%